Gas-Chromatographic Analysis of Mixtures of Hydrogen Isotopes Using Different Samples Loops - PREDA, ANISOARA; VASUT, FELICIA; STEFANESCU, IOAN; DAVID, CLAUDIA; PICIOREA, IULIANA; BARBU, CRISTINA; SBIRNA, SIMONA; PINTILIE, SOFIA (Asian Journal of Chemistry, 2010)
In this paper, the analysis of different mixtures of hydrogen isotopes using capillary molecular sieve 5 Å column and different sample loops are reported. It is realized a comparative study to develop or improve existing methods for the qualitative and quantitative determination of the composition of gas mixtures of hydrogen isotopes. The results are presented in chromatograms for different H2, HD, D2 mixtures and different operated parameters